Determining the effectiveness of digital reference services in selected academic libraries in Malaysia / Wan Ab. Kadir Wan Dollah - Wan Ab. Kadir , Wan Dollah (2008)
New technologies have been used to assist in a variety of functions in library and information units including in the provision of reference services. Digital reference services (DRS) are becoming widely available in Malaysian academic libraries and primarily provide assistance to remote users mainly through e-mail format. This study examined the existing status and effectiveness of digital reference services (DRS) in four selected public academic libraries in Malaysia. The study focused on the awareness, usage, usersï¿½ perception, usersï¿½ satisfaction, libraryï¿½s performance, and looked at the perceived needs, issues and problems faced by librarians and students. The study is important to determine how academic librarians are exploiting the latest information and communication technologies to improve reference service operations. The research methodology employed was a case study approach that combined three data collection methods, i.e. questionnaires, interviews and content analysis. Two different sets of questionnaires were distributed: (a) a librariansï¿½ questionnaires to 163 librarians, and (2) a usersï¿½ questionnaires to 1,000 students in four public universities in Malaysia. Structured interviews and systematic observations were conducted to collect information on the existing library services provided. The findings indicate: (a) all the four public academic libraries in Malaysia have implemented asynchronous DRS in the forms of e-mail reference and web forms; however, the extent of these services varies from institution to institution; (b) a majority (67.3%) of the students were aware of the university library offering DRS; (c) a majority (82.8%) of the librarians have been using DRS in answering reference questions; (d) a high percentage (73.1%) of librarians, but a small percentage (19.5%) of students have been using e-mail reference; web forms have been used by 32.3% of librarians and 28.2% of students; Ask-A Librarian have been used by 26.9% of librarians and 26.8% of students; (e) the digital reference services are effective form of service delivery in Malaysian academic libraries based on the findings on usersï¿½ perception, usersï¿½ satisfaction and libraryï¿½s performance; (f) the majority of the respondents would choose traditional reference (47%), but predicted online chat reference (42.7%), e-mail reference (37.4%) and video conferencing (36.5%) to be the most heavily used of reference services in the next five years. Recommendations are made on the need for the implementation of synchronous DRS, enhancing the role of DRS, marketing and promotion, staff training, user education programmes and cooperation. The main contribution of this research is the assessment of effectiveness of DRS in academic libraries in Malaysia, the identification of perceived needs, issues and problems and suggestions on the areas of improvement in the use of DRS. In the process, a proposed guideline for an effective DRS in academic libraries in Malaysia is presented. Finally, the researcher proposes directions for future research in the area of DRS.